Long-Term Culture of Organotypic Hippocampal Slice from Old 3xTg-AD Mouse: An ex vivo Model of Alzheimer’s Disease - Jang, Sooah (Psychiatry Investig, 2018)
OBJECTIVE: Conventional methods for organotypic hippocampal tissue slice culture (OHSC) have shown several disadvantages or limitations regarding age of animals used, duration of culture and difficulty using neurodegenerative models. Therefore, we tried to establish OHSC from old 3xTg-Alzheimer’s disease (AD) mice for longer period (over 4 weeks) and to validate utility of this system as a valid platform for translational neuroscience of AD. METHODS: OHSC was performed with old 3xTg-AD mice (12–14 months), old wild type mice (12–14 months) and young 3xTg-AD mice (2–4 months) using serum-free medium for 4 weeks. Hippocampal structure was evaluated by 4’, 6-diamidino-2-phenylindole (DAPI) intensity and neuronal metabolism was measured by Alamarblue assay. Pathologic characteristics of AD were also investigated; β-amyloid levels by ELISA, amyloid plaque deposition by Thioflavin-S staining, and glial activation by immunohistochemistry. RESULTS: Following 4-week culture in serum-free media, hippocampal cells and layers were well preserved in cultured slices from old AD mice as was in those from young AD and old wild type mice. On the contrary, excessive regression of total visible cells was observed in conventional serum-containing medium regardless of genotype of mice. In parallel with this well preserved structure, major pathologic characteristics of AD were also well manifested in hippocampal slices from old AD mice. CONCLUSION: Our findings suggest that long-term OHSC from old 3xTg-AD mouse can serve as a promising ex vivo system for studies on pathophysiology of AD, especially with the minimum number of sacrifice of experimental animals.